Effects of GADL1 overexpression on cell migration and the associated morphological changes - Wu, Tai-Na; Chen, Chih-Ken; Liu, I-Chao; Wu, Lawrence Shih-Hsin; Cheng, Andrew Tai-Ann (Scientific reports, 2019)
Lithium has been used for maintenance treatment of bipolar disorder, but drug response varies among patients. Single-nucleotide polymorphisms in glutamate decarboxylase–like protein 1 ( GADL1 ) are found to be associated with lithium response in Han Chinese bipolar patients. In this study, we assessed GADL1 function using a neuroblastoma cell line that stably overexpressed GADL1. Genes encoding factors involved in cell migration, such as FN1 , ITGA2 , ITGAV and CCL2 , were downregulated in GADL1 -overexpressing cells. GADL1 overexpression indeed suppressed cell migration. Cell migration speed and perimeter length exhibited similar trends, both of which were decreased under GADL1 overexpression or lithium treatment but increased upon stimulation with CCL2. Secreted GADL1 or its enzyme product, taurine, in the conditioned medium might exert only mild effects on the observed changes. Compared with SH-SY5Y cells, GADL1 -overexpressing cells were much more sensitive to CCL2 treatment but less sensitive to lithium, indicating that the level of GADL1 expression can affect cell sensitivity to lithium or  CCL2 treatment. Together, these results suggest that cell migration and related morphological changes might provide good indicators of the sensitivity toward lithium treatment, and the GADL1 stable overexpression cell line might serve as a useful platform to screen novel therapeutics for bipolar disorder.